Analysis of the Impact of the Implementation of the Government's Zero ODOL Policy in 2023 on Commodity Distribution in the Special Capital Region of Jakarta and West Java Provinces - Gultom, Simon; Datu Nabolon; Sarinah Sarinah; Prima Widianto; Yuwono Dwisilo Sucipto (Dinasti Publisher, 2024)
Abstract - The phenomenon of ODOL became a public and government highlight when, according to the data of the Ministry of Public Works and People's Housing (PUPR), the state losses due to ODOL trucks turned out to have reached Rs 43 trillion in accordance with the budget of annual expenditure of the PUPR Ministry. Since the initial announcement of the Indonesian policy Free of Vehicles Over Dimension and Over Load (ODOL) in 2023, it has received a varied response from the parties directly related as well as various layers of society, but the opinion is to implement the total Zero ODOL since the beginning of the year 2023 without exceptions and other opinions of the implementation of zero ODOL to be postponed in the period 2023-2025. Demos related to the rejection or request for the delay of the Zero Odol policy are becoming more pronounced at the end of this. The hopes of the people of DKI Jakarta and West Java provinces are that the distribution needs of important commodities are routine and must not be interrupted, the implementation of which will depend heavily on a transport fleet that has sufficient volumes of demand. The closer to the implementation of the government's Zero ODOL policy, the more the government needs to step up its efforts to keep the situation under control, ensuring that no accumulation becomes anarchic, widespread, or jeopardizes or interferes with the distribution of commodities to the public . This research aims to obtain answers on the impact of commodity distribution on DKI Jakarta Raya Province and West Java Province with the implementation of the Free ODOL policy in 2023, as well as the readiness of carriage entrepreneurs and fleet owners to meet the free ODOL regulation in 2023. This research uses qualitative methods with data collection techniques such as observations, interviews, documentation, and combination/triangulation. With the triangulation of sources, techniques, and time, as well as data analysis methods, the Miles and Huberman Interactive Model is an option to answer the problems that have already been formulated .